Entre júbilo e ruína: a perspectiva trágica de Nietzsche - Lima, Joana Brito de (2007)
It is investigating why reason Nietzsche affirms, in 1888, when revises his work (Ecce Homo), that to be exactly with The Birth of Tragedy it will be necessary to forget some things , and, in spite of, insist, in the same writing, in naming himself the first tragic philosopher - that is, the opposite and antipode of a pessimistic philosopher . Nietzsche elaborates in The Birth of Tragedy a theory about tragic starting from the opposition and complementarity among Apollo and Dionysian, rationalism and instinct, and in the refusal of the pessimistic perspective. The objective of the dissertation is to discuss how the theory of tragedy modifies due to the rupture with the inspiring of the first moment of the nietzschian philosophy, Schopenhauer and Wagner - maybe the such things to be forgotten about The Birth of Tragedy - and the implications of this rupture, that transforms the philosophy of Nietzsche in dissident of the metaphysical tradition. Like this, it is noticed that there is more continuity than estrangement in what concerns to the definition of tragic, just announced in 1871. By the sentence of the eternal return to the concept of will of power Nietzsche elaborates a tragic perspective, marked by the Dionysian celebration of the life, also acted through the pessimism dionisiac , defined in Gaya Science's § 370 (1881-2), and of the sentence of the love fate, enunciated in the §276 of the same work; all those concepts, discussed in this research, concentrate, decisively, the acceptance idea and statement of life, or more precisely, the decline of the tragic hero, between joy and ruin